Proceedings of the 14th Annual Conference Companion on Genetic and Evolutionary Computation 2012
DOI: 10.1145/2330784.2330869
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a feature-deselective neuroevolution classifier (FD-NEAT) in a computer-aided lung nodule detection system for CT images

Abstract: Systems for Computer-Aided Detection (CAD), specifically for lung nodule detection received increasing attention in recent years. This is in tandem with the observation that patients who are diagnosed with early stage lung cancer and who undergo curative resection have a much better prognosis. In this paper, we analyze the performance of a novel feature-deselective neuroevolution method called FD-NEAT to retain relevant features derived from CT images and evolve neural networks that perform well for combined f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Feature deselective-NEAT (FD-NEAT) follows an evolutionary feature selection strategy similar to FS-NEAT, but biases the subset search to favor larger selected feature subsets [48,49]. The FD-NEAT algorithm begins with a fully connected network just as NEAT does, and then removes connections via a remove connection mutation operation during evolution.…”
Section: Fd-neatmentioning
confidence: 99%
“…Feature deselective-NEAT (FD-NEAT) follows an evolutionary feature selection strategy similar to FS-NEAT, but biases the subset search to favor larger selected feature subsets [48,49]. The FD-NEAT algorithm begins with a fully connected network just as NEAT does, and then removes connections via a remove connection mutation operation during evolution.…”
Section: Fd-neatmentioning
confidence: 99%
“…29,30 NEAT's performance has been analyzed and proven in various and diverse domains. 28,[31][32][33][34][35] Recently, it was shown that Phased Searching with NEAT in a Time-Scaled Framework 26 and another variant of NEAT (feature-deselective NEAT or FD-NEAT) 36,37 performed well in a lung nodule detection scheme of CT images. The advantage of Phased Searching over conventional NEAT is that feature selection is enabled in Phased Searching, and it produces simpler networks than FD-NEAT and NEAT, which are faster to train and validate, and require less parameter (connection weight) tuning.…”
Section: Introductionmentioning
confidence: 99%